9/7=11/8x+3

Simple and best practice solution for 9/7=11/8x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9/7=11/8x+3 equation:


x in (-oo:+oo)

9/7 = (11/8)*x+3 // - (11/8)*x+3

9/7-((11/8)*x)-3 = 0

(-11/8)*x+9/7-3 = 0

-11/8*x-12/7 = 0 // + 12/7

-11/8*x = 12/7 // : -11/8

x = 12/7/(-11/8)

x = -96/77

x = -96/77

See similar equations:

| -7x=-5x-10 | | 4x+7-3x+6= | | 4(34+9x)+16x=32 | | 5x+2(3x-7)=-20+11x+6 | | 10x+x= | | -12b+6b-4b= | | 3/4=x/4 | | 9(16x+4y)+34=32 | | 25m^2-25= | | t=13+x | | 9+2/5=29-11/7 | | 2/-5=6/t | | 3+3x=-6+2x | | t^6-36= | | 1.5x-2.6=3.4 | | 62d-1+13=19 | | x+2x-12+x=-3+2x | | C+1/c-2=4/6 | | (5-x)(2x+3)(x+6)=0 | | 9+2.7t=-4.8t-8 | | 27-x=18.9 | | 9x+81=4x-24 | | 200=5x+55+5x+45 | | 3/4x=6/8 | | 3n+6=5n-12 | | 4x-x=b | | x+2x-12=x+7 | | 8j-5+j=14.2 | | -5(4y-8)+4(3y+8)= | | 9x+45=3x+27 | | 27=18.9+x | | 17x=-3/4 |

Equations solver categories